Pemberdayaan Kader Remaja Dalam Kampanye Aku Bangga Aku Tahu Cegah HIV/AIDS - Diah Ratnawati; Sang Ayu Made Adyani; Dora Samaria (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aims to increase knowledge, perception, reduce stigma and improve HIV/AIDS prevention and control behavior among youth cadres. The PKM method is carried out through a group process, through the formation of youth cadres, provision of cadres through health education, health education techniques and roleplay. This program carried out in partnership with sub district Meruyung Depok, teenagers, parents, ans Puskesmas Meruyung officers. The result of this PKM activity is the formation of 2 groups of teenage cadres consisting of 40 people. The evaluation of PKM activities using a pre-test and post-tes questionnaire found that there was an increase in knowledge, attitudes, and behavior before and after the youth cadres were given PKM activities.